BIBLIOMETRIC ANALYSIS OF DIGITAL TRANSFORMATION SUCCESS - Sitinjak, Manuntun; Irawan, Agustinus Purna (Graduate Program of Universitas Tarumanagara, 2023)
Digital Transformation is a hot and trending topic, and many organizations are trying to learn and implement. Some of them are successful, but there are also those who have not succeeded in carrying out Digital Transformation. There are quite numerous articles and researches on Digital Transformation Success, yet none of them focus on how Successful Digital Transformations Standard should be developed. For this reason, it is necessary to map the articles and research progress on this topic by carrying out a Bibliometric Analysis. We found 76 articles focusing on Digital Transformation Success by “title” published between 1996 to 2022 with search strings (“digital transformation” AND success). With this methodology we identified how authors have made collaborations on this topic and most related significant terms. The present study provides insight and reveals what things have been explored and discussed, and we found a necessity for further research with a purpose of determining a Reliable Standard for Successful Digital Transformation. However, this paper has limitations because it is only based on Google Scholar database.